THE USE OF AUDIO-VISUAL MEDIA IN SPEAKING ABILITY OF ENGLISH SPEAKING CLUB STUDENS AT STMIK ROYAL KISARAN - Akmal Akmal (Smart Education, 2019)
Audio-visual media is a method to produce or deliver the materials by using mechanical and electronic machines to present audio-visual messages. Teaching through audio visual media is clearly characterized by the use of hardware during learning such as television, tape recorder, and wide visual projector. In this English speaking learning using video media, infocus, and laptop. The material is given in the form of overall English. The researcher presented several films about English and the English Speaking Club for Students students were very passionate and responded positively so that they were able to speak in English by communicating entirely in English. They are also more interactive in speaking English. The students’ speaking ability got the progress so significant and can improve their speaking skill in English.